Synthesis of flavonoid 2-deoxyglucosides via the Mitsunobu reaction. Issue 42 (17th October 2018) - Han, Ziyi; Zheng, Zhiwei; Cai, Li; Zhou, Dandan; Li, Changsheng; Sui, Qiang; Liu, Shuai; Gao, Qi
Graphical abstract: Highlights: Glycosylation of 7-OH flavonoids was achieved via the Mitsunobu reaction. Various flavonoid 2-deoxyglucosides were generated. Stereoselectivity was observed as mainly controlled by the sugar protecting groups. Abstract: The Mitsunobu reaction of flavonoids and 3, 4, 6-tri- O -acetyl-2-deoxy-d -glucopyranose or 3, 4, 6-tri- O -benzyl-2-deoxy-d -glucopyranose is a very effective method for the stereoselective synthesis of flavonoid 2-deoxyglucosides. Since there is no C2 substituent on the sugar moieties, the observed α- or β-stereoselectivity was mainly controlled by the (acetyl or benzyl) protecting groups. Possible mechanistic insights are offered to explain the dual stereoselectivity.